Celebrating diversity: deconstructing and reconstructing curriculum for inclusion and multiculturalism in the uteq teacher training program - Beltrán Marín, Andrea Victoria (2025)
Diversity and inclusion are fundamental aspects of teacher training, as they prepare educators to respond to the needs of multicultural environments. This research aimed to propose a cross-curricular strategy for curriculum modification in the UTEQ Teacher Training Program, integrating principles of inclusion and multiculturalism into all subjects. A mixed-methods approach with an exploratory sequential design was adopted. Surveys were conducted with 48 students, and interviews were conducted with 7 professors, using descriptive and thematic analysis to interpret the data. The results indicated that while the curriculum addresses diversity, its integration is not consistent across all subjects. Students highly value the importance of understanding diversity for their professional development but expressed a need for more multicultural content. On the other hand, professors highlighted the lack of resources and clear strategies to effectively incorporate these approaches into their teaching. In conclusion, the need to reformulate the teacher training curriculum was identified through a strategy based on deconstruction and reconstruction theory, ensuring a more inclusive education that represents diverse cultural realities.